Pelatihan Statistik Dalam Upaya Peningkatan Kemampuan Penalaran Siswa SMK Avicena Tenjo - Irvana Arofah; Besse Arnawisuda Ningsi (Jurnal Gembira: Pengabdian Kepada Masyarakat, 2023)
This Community Service aims to provide alternative solutions to the problems faced in improving students' reasoning abilities. The methods used in carrying out this service include the following: Procurement of initial evaluations to determine the initial abilities of the Avicenna Tenjo Vocational High School students, Statistical training using the SPSS and Minitab applications, Training for completing statistical sample questions using the SPSS and Minitab applications, Final evaluation in the form of level of knowledge and mastery of Avicenna Tenjo Vocational High School students after being given this dedication material. An increase in student reasoning occurs when students are given examples of existing applications in everyday life and with interesting delivery. An increase in students' reasoning occurs when the use of information technology is used in statistical materials, using SPSS and Minitab software. Students are more stimulated to find out every detail of the material when students practice the material directly using SPSS and Minitab software.